Integrasi Pasar Berjangka Komoditi Crude Palm Oil (CPO) Indonesia Di Masa Pandemi Covid-19 - Octaviana Helbawanti; Cici Aulia Permata Bunda; Faqihuddin Faqihuddin (Universitas Medan Area, 2022)
Crude Palm Oil (CPO) commodity trading has been carried out domestically and exported, so that theprice developments formed are domestic trading prices in the spot market and global prices ininternational market level. Price fluctuations in CPO agriculture increased the risk of trade causinguncertainty in the spot market and derivatives market. Price uncertainty was the impact of theinability of a market to follow the price changes in other markets. Research on CPO prices in thederivatives market and spot market was aimed to analyze market cointegration and causality.Johansen Cointegration Test and the Granger Causality Test were applied to this research. TheJohansen Cointegration test results explained that the derivatives market and the spot market ofCrude Palm Oil (CPO) were not long-term cointegrated. The Indonesian CPO market has not been ableto become an international reference market due to derivative transactions and lack of literacy. Thespot market that was unable to follow the movements of the derivatives market might be caused byprice fluctuations due to uncertainty during the Covid-19 pandemic with social restrictions on globaltrade activities. There was one-way causality from the analysis using Granger Causality. The causality test depicted the derivatives market affected the spot market, so that changes or shocks in thederivatives market could be transmited into spot market. The derivatives market at the global levelheading to Rotterdam as a market leader showed price discovery function, while the Indonesian spotmarket became market follower. The demand of CPO in the European market was high for biofuelsand many industral purposes and there were regulations on the use of CPO which have contributedto the influence of the spot market in Indonesia. The derivative market provided future priceinformation intended minimize the uncertainty of price changes.